Evaluating the impact of the diagnosis-related groups payment system on laparoscopic uterine fibroid surgery outcomes: insights from a single-center study - Lu, Jingjing; Pan, Yiming; Li, Lu; Chu, Lili; Jin, Yanshan (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to assess the impact of implementing the diagnosis-related groups (DRGs) payment system on hospitalization costs and medical service outcomes at a single institution. The objective was to identify effective cost-saving strategies and guide healthcare practices to support the ongoing adoption of the DRGs system.MethodsThis retrospective study included 616 patients, categorized into three groups based on the payment system in effect during their treatment: a 6-month period under fee-for-service (FFS), a 6-month period following the trial implementation of DRGs (TI-DRGs), and a 6-month period after the official implementation of DRGs (OI-DRGs). Each group was further divided into two subgroups according to the surgical intervention received (either laparoscopic myomectomy or laparoscopic hysterectomy). Data collected included total medical costs, examination fees, surgical costs, medication and supply expenses, length of hospital stay, operation time, intraoperative blood loss, incidence of postoperative anemia, and frequency of blood transfusions.ResultsTotal medical costs in the OI-DRGs group were 6.6 and 9.0% higher than those in the FFS and TI-DRGs groups, respectively (p < 0.001). Examination costs followed a similar pattern, with the OI-DRGs group showing increases of 5.3 and 12.3% compared to the FFS and TI-DRGs groups (p < 0.001). Operation costs also varied significantly among the three groups; the OI-DRGs group incurred 17.1 and 10.5% higher costs than the FFS and TI-DRGs groups, respectively (p < 0.001). There were no significant differences among the groups in terms of hospital stay duration, operation time, or intraoperative blood loss. In the FFS group, 57 patients developed postoperative anemia and 14 required blood transfusions; in the TI-DRGs group, 52 patients developed anemia and 16 received transfusions; and in the OI-DRGs group, 74 patients developed anemia with 16 requiring transfusions. However, these differences were not statistically significant.ConclusionIn summary, the implementation of DRGs for laparoscopic uterine leiomyoma surgery did not lead to a significant reduction in total medical costs. Overall costs were influenced by multiple factors, including the DRG phase, length of stay, type of surgery, and the presence of concurrent procedures. The findings from our single-center study differ from the mainstream view, highlighting that the effects of DRG implementation can be highly context-specific, shaped by local policies, hospital practices, and patient case-mix, which may limit the generalizability of these results beyond our institution or region.